Family Center Care Management for Outpatients in the New Era - Pratiwi, Etik; Susilo Adi, Giri (International Journal of Nursing and Health Services (IJNHS), 2022)
Introduction: Hospitalization can generally occur in sick children, requiring the child to stay in the hospital to undergo therapy and treatment until discharge back home. Patient and family-centered care (PFCC) or Family Care Centered is an approach to planning, implementing, and evaluating health care based on mutual benefits. Objective: The study aimed to examine the effect of Family Center Care management on Outpatients in the New Era Method: The research was applied using a pre-experimental design method with a pre-posttest. The sample of the study was 45 patients who were taken from a medical and rehabilitation clinic in the Yogyakarta area. Results: Results: The data analysis using a paired sample T-test with an average FCC pretest score of 78.313 and an average FCC post-test score of 79,980. The test results showed a p-value of 0.004. A P value of less than 0.005 indicated that the FCC program affected the patient's recovery. Recommendation: This study provides a recommendation that it is important for family center care support to be provided by health workers to sick family members so that they can accelerate the healing process